2010
DOI: 10.1007/s11010-010-0695-z
|View full text |Cite
|
Sign up to set email alerts
|

Gomisin N enhances TNF-α-induced apoptosis via inhibition of the NF-κB and EGFR survival pathways

Abstract: Tumor necrosis factor (TNF-α) is a pleiotropic cytokine that plays an important role in the control of cell proliferation, differentiation, and apoptosis. TNF-α-induced apoptosis is limited by TAK1-mediated activation of NF-κB (mainly p65-p50 hetrodimer) signaling pathway. We have recently reported that TAK1 regulates phosphorylation of EGFR at Ser-1046/7 through p38 MAPK, which cooperates with NF-κB in TNF-α-induced apoptosis. The present study investigated the effect of gomisins A and N, dibenzocyclooctadien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…It was reported that gomisin N, a dibenzocyclooctadiene lignan similar to gomisin A, suppressed the NF-κB signaling pathway in HeLa cells. 8) These results suggest that inhibition of p-IκB and NF-κB reactions by gomisin A resulted in inhibition of the expression of pro-inflammatory mediators. It has been reported that gomisin A does not inhibit CCl(3) radical formation caused by CCl 4 induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…It was reported that gomisin N, a dibenzocyclooctadiene lignan similar to gomisin A, suppressed the NF-κB signaling pathway in HeLa cells. 8) These results suggest that inhibition of p-IκB and NF-κB reactions by gomisin A resulted in inhibition of the expression of pro-inflammatory mediators. It has been reported that gomisin A does not inhibit CCl(3) radical formation caused by CCl 4 induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, a number of studies have shown that gomisin A has various pharmacological functions, including enhancement of tumor necrosis factor (TNF)-α-induced apoptosis, vascular relaxation, memory improvement, reduction of neuronal damage, and improvement of insulin sensitivity. [8][9][10][11][12] In addition, gomisin A showed a hepatoprotective effect in various animal models of hepatotoxicity including CCl 4 , acetaminophen and lipopolysaccharide (LPS) as well as promoting liver regeneration after partial hepatectomy. [13][14][15][16] However, the precise molecular mechanism of the hepatoprotective effects has not been comprehensively explored.…”
mentioning
confidence: 99%
“…Trimerization of the death domain leads to the recruitment of an adaptor molecule, FADD, and subsequent activation of caspase-8 and caspase-10, which in turn leads to the cleavage of caspase-3 and death substrates (9,11,12). Previous studies indicated that TNF-α induced cell death through caspase-3 activation and PARP cleavage (36,37). It has been reported that caspase-8 activation was observed in the TRAIL-induced apoptosis of HeLa cancer cells (11,31).…”
Section: Discussionmentioning
confidence: 99%
“…In the death receptor pathway, nuclear factor-κB (NF-κB), a well-known transcription factor, protects cells from apoptosis by the activation of survival factors such as anti-apoptotic proteins (43). It has been shown in HeLa cells that the inhibition of NF-κB can sensitize the cancer cells to TNF-α-and TRAIL-induced apoptosis (29,31,37). The present results showed that the ethanolic extract of T. peruviana flowers had no effect on TNF-α-induced NF-κB activation (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…32,33) We previous demonstrated that gomisin N, but not gomisin A, inhibited the TNF-α-induced NF-κB and epidermal growth factor receptor (EGFR) signaling pathways in HeLa cells, which resulted in enhanced pro-apoptotic events. 34) However gomisin A also inhibited cell proliferation; therefore, in this study, we investigated the molecular mechanisms of the antiproliferative effect of gomisin A in TNF-α-treated HeLa cells.…”
mentioning
confidence: 99%